Expression of SIRPα-Fc by oncolytic virus enhances antitumor efficacy through tumor microenvironment reprogramming - Yang, Qingzhe; Shu, Yongheng; Chen, Yanwei; Qi, Zhongbing; Hu, Shichuan; Zhang, Yao; Qin, Yu; Xu, Xianglin; Hu, Jianchuan; Huang, Anliang; Cheng, Ping (Frontiers in Immunology, 2025)
Oncolytic viruses (OVs) selectively replicate within tumors, directly killing cancer cells and promoting a systemic immune response by releasing tumor antigens. These features make OVs a promising approach in tumor immunotherapy, offering targeted treatment with fewer side effects. Despite these advantages, OVs are primarily administered via intratumoral injection, limiting their effectiveness for advanced, systemic cancers. Among OVs, oncolytic adenoviruses (oAdVs) are the most widely studied due to their well-understood gene regulation, safety, and stability. In this study, a modified oAdV vector, pDC316-oAd-SA, was engineered to express the SIRPα-mIgG1Fc gene, designed to remodel tumor-associated macrophages (TAMs) and enhance anti-tumor immunity. This vector, along with a control virus (Ad-ON), was evaluated both in vitro and in vivo. The modified oAd-SA significantly improved macrophage phagocytosis and showed superior tumor regression in murine models. Additionally, while both oAdVs increased T cell infiltration in the tumor microenvironment, oAd-SA specifically enhanced T cell immune function. The study also revealed that oAdVs modulate TAMs differently across tumor types, with oAd-SA therapy particularly increasing TAM phagocytosis and promoting an anti-tumor response.